Arctic amplification: does it impact the polar jet stream?. Issue 1 (1st December 2016) - Meleshko, Valentin P.; Johannessen, Ola M.; Baidin, Andrey V.; Pavlova, Tatiana V.; Govorkova, Veronika A.
Abstract : It has been hypothesised that the Arctic amplification of temperature changes causes a decrease in the northward temperature gradient in the troposphere, thereby enhancing the oscillation of planetary waves leading to extreme weather in mid-latitudes. To test this hypothesis, we study the response of the atmosphere to Arctic amplification for a projected summer sea-ice-free period using an atmospheric model with prescribed surface boundary conditions from a state-of-the-art Earth system model. Besides a standard global warming simulation, we also conducted a sensitivity experiment with sea ice and sea surface temperature anomalies in the Arctic. We show that when global climate warms, enhancement of the northward heat transport provides the major contribution to decrease the northward temperature gradient in the polar troposphere in cold seasons, causing more oscillation of the planetary waves. However, while Arctic amplification significantly enhances near-surface air temperature in the polar region, it is not large enough to invoke an increased oscillation of the planetary waves.